Arterial stiffness is associated with oxidative stress and endothelial activation among persons with treated HIV in Zambia - Theresa Chikopela; Fastone Goma; Longa Kaluba; Wilbroad Mutale; Chris Guure; Douglas C. Heimburger; John R. Koethe (AOSIS, 2021)
Background: Cardiovascular disease (CVD) prevalence is rising among persons with HIV (PLWH) in sub-Saharan Africa. Oxidative stress and endothelial activation, resulting in reduced vascular compliance, are contributors to CVD risk. However, there is a paucity of vascular health data in this population. Objectives: To assess the relationships of oxidative stress and endothelial activation with vascular stiffness among PLWH. Method: Fifty-four PLWH on antiretroviral therapy 5 years and 57 HIV-negative controls, all aged 18-45 years, were enrolled from the University Teaching Hospital, Lusaka, Zambia. Oxidative stress was measured by nitrotyrosine, a peroxynitrite biomarker, and endothelial activation by soluble intercellular adhesion molecule-1 (sICAM-1) plasma levels. Vascular compliance was measured using carotid-radial pulse wave velocity (crPWV) and arterial stiffness index (crASI). Results: PLWH had higher sICAM-1 levels (median 345 ng/mL) compared to controls (275 ng/mL, p 0.01), as well as higher nitrotyrosine levels (297 versus 182 nM; p = 0.02). Median crPWV was similar between the groups, but PLWH had higher crASI (2.4 versus 2.2 cm/ms; p 0.05). After adjusting for age, fat mass, and blood pressure, the estimated effect of a one unit increase in nitrotyrosine on crPWV were twofold higher in the PLWH, but neither reached significance. In a model pooling all participants, there were significant differences in the relationship of nitrotyrosine with crPWV and crASI by HIV status. Conclusion: PLWH in sub-Saharan Africa had significantly greater oxidative stress and endothelial activation compared to HIV-negative individuals. These factors may contribute to increased arterial stiffness and higher CVD prevalence in this population.